Philosophical Peer disagreement - Lo Guercio, Nicolás Francisco (2012)
It has been widely discussed, in recent years, which is the rational doxastic reaction in the face of peer disagreement. But not much has been said about aninteresting instance of that debate: philosophical peer disagreement. That is precisely what I will be concerned with in this paper. First, I will offer a definition ofphilosophical peer that introduces the idea of an epistemic perspective. The proposed definition allows for a doublé distinction: between Strong and Weak Peers, and between Strong and Weak Disagreements. Based on these distinctions, I will defend that different doxastic reactions are required depending on the type of disagreement at issue. On the one hand, in the face of Weak Disagreement, we should be conciliatory. Cases of Strong disagreement, in turn, shouldn’t motívate a doxastic revision. In order to argue for that, some refinements into the notion of Rational Uniqueness will be needed.